IDENTIFIKASI FENOTIPIK GALUR-GALUR KEDELAI TERHADAP KETAHANAN SERANGAN HAMA ULAT GRAYAK (SPODOPTERA LITURA F.) - Gatut Wahyu Anggoro Susanto; Moh. Muchlish Adie (Universitas Lampung, 2015)
Phenotypic identification of soybean lines against armyworm pest resistance (Spodoptera litura F). This research consisted of two parts which aimed to find out the intensity of damage to the leaves and the influence of soybean on the biological aspect of armyworms. The materials tested were Shr/W-C-60, Aochi/Wil-60, 9837/K-D-8-185, 9837/K-D-3-185-95, W/9837-D- 6-220, 9837/K-D-3-185-82, 9837/W-D-5-211, GI, G100H breeding lines and Wilis varieties. The research was conducted at a Balitkabi screenhouse in February 2011, using randomized block design and each treatment was replicated three times. The planting media were plastic pots (diameter 18 cm) filled with earth, two seeds per pot were planted and intensively raised. When the plants were 27 days old after planting, at each replication consisting of 10 materials, they were covered with gauze cages (2 x 2 x 2 m). Then the plants in each pot was infested with 10 instar I armyworm larvae. The other part of research was carried out in Balitkabi Breeding Improvement Laboratory. For testing purposes, there was a need for a third nodal leaf of soybean aged 27 days after planting in each tested material. The research used a completely randomized design each treatment was replicated three times. One nodal leaf in each material was placed in a petri dish 15 cm in diameter, which was coated with moist filter paper, and this was later called treatment. Each treatment was infested with one instar I armyworm larva. The result of research indicated that an assessment of soybean resistance to armyworms could be made from the density of the trichome and/or the length of the trichome on the leaves. The G100H breeding line was found to be resilient with its characteristics of having dense trichome (25/4 mm2) and long trichome (1.1 mm).